Gas-Diffusivity Measurement in Reservoir Fluid at Elevated Pressures Systems for Transient Shut-In Modeling - Zainal, Suzalina (2010)
Gas-liquid diffusivity is investigated for many different oil recovery applications. Most interest is in the gas-oil diffusivity for enhanced oil recovery applications such as miscible gas flooding, immiscible carbon dioxide WAG (Water-Alternating-Gas) flooding and non-thermal heavy oil recovery by solvent injection. Other study includes the analysis of gas-water diffusivity to understand the methane hydrates formation. In designing an enhanced oil recovery process, for instance, further information on the rates and amount of mass transfer by diffusion is required. The focus is to have better insight of the mass transfer mechanisms, particularly at the reservoir level.